The effect of mental training with biofeedback on the performance of young swimmers - Bar-Eli, M.; Dreshman, R.; Blumenstein, B.; Weinstein, Y. (Applied Psychology, 2002)
The purpose of the present study was to investigate the relationship between mental training with biofeedback and performance. An adapted version of the Wingate five-step approach was used as a mental preparation technique for enhancing the swimming performance among 11-14-year-old children swimmers. Participants (n= 38) were randomly assigned to one of two conditions: (a) experimental—regular training plus three stages of the Wingate mental training program, and (b) control—regular training and relaxing activities. After a baseline measurement, participants were tested on evaluation scores and actual performance twice during a 14-week period. Results indicated that the experimental group exhibited a greater increase in performance, although the control group also displayed some improvements. Results are discussed in reference to previous work on the Wingate approach to mental training. In addition, several methodological and theoretical aspects are discussed that are particularly relevant to the use of such interventions with other athletic tasks among children, adolescents, and adults. Das Ziel der vorliegenden Studie war es, die Beziehung zwischen mentalem Training mit Biofeedback und Leistung zu untersuchen. Eine angepasste Version des Wingate-Fünf-Stufen-Ansatzes wurde als mentale Vorbereitungstechnik zur Verbesserung der Schwimmleistung bei 11-14-jährigen Kindern verwendet. Die Teilnehmer (n= 38) wurden nach dem Zufallsprinzip einer von zwei Bedingungen zugeordnet: (a) experimentelles, regelmäßiges Training plus drei Stufen des Wingate-Mentaltrainingsprogramms, und (b) kontrolliertes, regelmäßiges Training und Entspannungsaktivitäten. Nach einer Ausgangsmessung wurden die Teilnehmer innerhalb von 14 Wochen zweimal auf ihre Bewertungsergebnisse und ihre tatsächliche Leistung getestet. Die Ergebnisse zeigten, dass die Versuchsgruppe eine größere Leistungssteigerung zeigte, obwohl auch die Kontrollgruppe einige Verbesserungen zeigte. Die Ergebnisse werden in Bezug auf frühere Arbeiten zum Wingate-Ansatz für mentales Training diskutiert. Darüber hinaus werden mehrere methodische und theoretische Aspekte erörtert, die für den Einsatz solcher Interventionen bei anderen sportlichen Aufgaben bei Kindern, Jugendlichen und Erwachsenen besonders relevant sind.